Association of apical rocking with long-term major adverse cardiac events in patients undergoing cardiac resynchronization therapy. - Ghani, Abdul; Paul, Peter; Delnoy, H. M.; Ottervanger, Jan Paul; Misier, Anand R. Ramdat; Smit, Jaap Jan J.; Adiyaman, Ahmet; Elvan, Arif (European Heart Journal - Cardiovascular Imaging, 2016)
AIMS: Correctly identifying patients who will benefit from cardiac resynchronization therapy (CRT) is still challenging. 'Apical rocking' is observed in asynchronously contracting ventricles and is associated with echocardiographic response to CRT. The association of apical rocking and long-term clinical outcome is however unknown at present. We assessed the predictive value of left ventricular (LV) apical rocking on a long-term clinical outcome in patients treated with CRT. METHODS AND RESULTS: Consecutive heart failure patients treated with primary indication for CRT-D between 2005 and 2009 were included in a prospective registry. Echocardiography was performed prior to CRT to assess apical rocking, defined as motion of the LV apical myocardium perpendicular to the LV long axis. Major adverse cardiac event (MACE) was defined as combined end point of cardiac death and/or heart failure hospitalization and/or appropriate therapy (ATP and/or ICD shocks). All echocardiograms were assessed by independent cardiologists, blinded for clinical data. Multivariable analyses were performed to adjust for potential confounders. Two hundred and ninety-five patients with echocardiography prior to implantation were included in the final analyses. Apical rocking was present in 45% of the study patients. Apical rocking was significantly more common in younger patients, females, patients with sinus rhythm, non-ischaemic cardiomyopathy, and in patients with LBBB and wider QRS duration. During a mean clinical follow-up of 5.2 ± 1.6 years, 92 (31%) patients reached the end point of the study (MACE). Patients with MACE had shorter QRS duration, had more ischaemic cardiomyopathy, and were more often on Amiodarone. In univariate analyses, MACE was associated with shorter QRS duration, ischaemic aetiology, and the absence of apical rocking. After multivariable analyses, apical rocking was associated with less MACE (hazards ratio, HR 0.44, 95% confidence interval, CI 0.25-0.77). CONCLUSION: Apical rocking is an independent predictor of a favourable long-term outcome in CRT-D patients.